State and Islamic response to the AIDS in Indonesia - Rahman, Hudriansyah; Faddad, Zaki (Indonesian Journal of Islam and Muslim Societies, 2012)
This paper explores the historical narrations of AIDS in Indonesia that shape itsconstruction. It will focus on the relation between Governmental and Islamicresponses to HIV/AIDS. In this research, we will focus on the governmental officialcommission on AIDS prevention (KPA) which is concern about HIV and AIDSand MUI as a government Islamic institution. This paper will argued that theresponses of both parties in the Indonesian ânarrationsâ of HIV/AIDS can influencethe practice of AIDS prevention. Government ways to treat AIDS in Indonesiahave changed overtime in line with the development of medical and socialwork efforts to cope with the problem of HIV/AIDS. However the Islamic institutionresponse in Indonesia does not change anymore and seems not to haveseriously attention in the issue of HIV/AIDS, it can be look from the unchangingMUIâs fatwa which is limited the problem of AIDS solely as morality problemMakalah ini akan menguraikan narasi historis tentang AIDS di Indonesia yangmembentuk konstruksi terhadap penyakit ini. Fokus masalah yang akan ditelitiadalah hubungan antara pemerintah dan kelompok Islam dalam merespon HIV/AIDS. Negara dalam hal ini diwakili oleh KPA (Komisi Penanggulangan AIIDS) danMUI (Majelis Ulama Indonesia) sebagai institusi Islam di bawah pemerintah.Makalah ini berargumen bahwa respon kedua kelompok tersebut tersaji dalam suatu narasi penjangkitan HIV/AIDS yang berpengaruh terhadap tindakanpenenanganan AIDS di Indonesia. Cara penanganan pemerintah terhadap AIDSdi Indonesia telah berubah sepanjang waktu sejalan dengan perkembangan medisdan upaya-upaya pada ranah pekerjaan sosial dalam mengatasi masalah AIDS.Namun sebaliknya, respon institusi Islam tidak berubah sama sekali, hal ini dapatdilihat dari fatwa MUI yang masih memandang persoalan AIDS sebagai persoalanmoralitas.